Of Intertwining and Untwining — In Exchange With Transculturality (KULT_online, 2023)
The volume Transkulturalität — Prozesse und Perspektiven by Jürgen Erfurt deals with cultural intertwining and untwining relations. With his book, Erfurt provides a successful overview of the current research situation and of the complexity behind the term transculturality. Erfurt comprehensively offers orientation for students which could well be used as a fundamental reference text in the future.